Violence Risk Assessment Tools Used in Forensic and Acute Psychiatry in North America: A Scoping Review - Maria Alexandra Rosca; Olivier La Charité-Harbec; Jeanne-Marie Allard; Stéphanie Borduas Pagé; Alexandre Hudon (Psychiatry International)
Violence in psychiatric settings presents a significant risk to patients, staff, and society at large. With over 400 risk assessment tools available globally, their applications and the risks they assess vary, allowing for diverse use in different situations. This scoping review investigated the risk management tools utilized in North America’s forensic psychiatry and acute psychiatric units, aiming to identify which ones are mainly used. A comprehensive search was conducted across PubMed, Embase, and PsycINFO databases, following PRISMA Guidelines, covering the literature from their inception date until 2023. Criteria for study inclusion required a focus on risk management tool use in forensic or acute psychiatric settings, originality (original studies, case reports, or systematic reviews), and a North American context. Out of 3059 identified studies, 40 were thoroughly analyzed. Commonly used risk assessment scales include HARM-FV, eHARM-FV, HCR-20, PCL-R, START, BVC, and DASA, with their reliability varying by the clinical context and the assessed population. The review highlights the heterogeneous application of static and dynamic scales across clinical settings, underscoring a need for more precise tools to improve risk assessments in forensic psychiatry, signaling a call for the development and validation of more sophisticated assessment instruments.